Pengaruh Influencer Marketing dan Brand Image Terhadap Minat Beli pada Produk Ms Glow di Gorontalo - Erika Hasan; Rizan Machmud; Umin Kango (Economic Reviews Journal, 2025)
Digital marketing strategies through influencers are increasingly popular, including in Gorontalo. MS Glow is one of the brands that has successfully leveraged this trend. Amidst the fierce competition in beauty products, brand image and influencer impact are considered to play a significant role in shaping consumer purchase intention. This study aims to determine the influence of influencer marketing and brand image on the purchase intention of Ms Glow products in Gorontalo. This research uses a descriptive quantitative method. Primary data were collected through questionnaires distributed to 100 consumers of Ms Glow products in Gorontalo, who were selected as respondents. The data collected were tested using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. Data analysis was carried out using SPSS Version 21. The results of the analysis show that both influencer marketing and brand image have a positive and significant effect on the purchase intention of Ms Glow products in Gorontalo. Influencer marketing contributes 14.2% to purchase intention (t-value = 2.571, ρ value = 0.012), while brand image contributes 67.7% (t-value = 9.331, ρ value = 0.000). Simultaneously, influencer marketing and brand image significantly affect purchase intention by 98.9% (F-value = 4,181.363, ρ value = 0.000, R Square = 0.989). It can be concluded that both Influencer Marketing and Brand Image have a positive and significant influence, both partially and simultaneously, on the Purchase Intention of Ms Glow Products in Gorontalo.